Role of the microbiome and its metabolites in ankylosing spondylitis - Song, Zi-Yi; Yuan, Duo; Zhang, Sheng-Xiao (Frontiers in Immunology, 2022)
Ankylosing spondylitis (AS), a chronic condition that commonly influences the spine and sacroiliac joints, usually progresses to stiffness and progressive functional limitation. Its fundamental etiology and pathogenesis are likely multifactorial and remain elusive. As environmental factors, gut microbiota performs critical functions in the pathogenesis of AS through various mechanisms, including interacting with genes, enhancing intestinal permeability, activating the gut mucosa immune system, and affecting the intestinal microbiota metabolites. This review provides an overview of recent advances in investigating gut microbiota in AS pathogenesis and discusses potential methods for future therapeutic intervention.